MANTENAN DI MADURA DALAM STRUKTURALISME LEVI-STRAUSS - Umam, Khairul (JURNAL SETIA PANCASILA, 2021)
Madura is one of the fourth largest tribes after the Malays, Javanese and Balinese who are an important wealth in Indonesia as a country with the largest number of ethnic in the world. Around 714 tribes with 742 regional languages ??with various cultures that live in them become their own colors that need to be maintained and continuously explored. Even though the mantenan in Madura. In Strauss' view of structuralism, to explore these treasures, it is necessary to understand the local language as a way of verbal or symbolic communication. Because in the mantenan tradition there is meaning to be revealed, both related to the way of life, outlook on life or behavior of the local community in the form of symbols. The method used in this research is descriptive qualitative approach, namely literature study, interviews, and data analysis and interpretation. From the results of the study, it is known that the mantenan tradition reveals two important things in the life of the Madurese community, namely balance and harmony. These two things are like two currencies that complement and fill each other so that a safe, peaceful, and prosperous society will be achieved.